Lead and cadmium contents of animal feed resources in Haryana - ., BHARATHIDHASAN; KAUR, S,HARJIT; MANI, VEENA; KEWALRAMANI, NEELAM (The Indian Journal of Animal Sciences, 2011)
A survey was conducted to assess the status of lead and cadmium in animal feeds in Haryana state. Concentrate ingredients (113), fodder (209), and paddy straw (80) and mineral mixture samples (8) were collected, randomly to cover industrial areas, areas along road sides as well as interior villages. The data obtained were classified into eastern (1) and western (2) zones as per agro-climatic conditions. Lead did not differ between the 2 zones. But, there was significant difference between zone 1 and zone 2 in cadmium content of both berseem and oats. Berseem samples from Gurgaon had highest lead content of 2.91 Â± 0.29 ppm as compared to other industrial districts. The cadmium content of berseem samples of Panipat and Sonipat districts was higher than other districts. The lead content of berseem was highest in samples grown near NH-2 (Delhi to Faridabad) followed by NH-8 (Delhi to Gurgaon), whereas in oats, the highest lead content was observed in samples collected from NH-l (Delhi to Ambala). There was no variation in the lead content of oats in different industrial districts. The levels of Pb and Cd in all the feeds were below the maximum permissible limits for livestock feeding. Lead concentration of 2 and Cd concentration of 5 out of 8 mineral mixture samples was above the maximum acceptable limits. Â